The synergistic compatibility mechanisms of fuzi against chronic heart failure in animals: A systematic review and meta-analysis - Liu, Xingyu; Xie, Xiaofang; Luo, Maozhu; Zhao, Yuting; Li, Mengting; Peng, Fu; Peng, Cheng (Frontiers in Pharmacology, 2022)
Background: Fuzi’s compatibilities with other medicines are effective treatments for chronic heart failure. Pre-clinical animal experiments have indicated many possible synergistic compatibility mechanisms of it, but the results were not reliable and reproducible enough. Therefore, we performed this systematic review and meta-analysis of pre-clinical animal studies to integrate evidence, conducted both qualitative and quantitative evaluations of the compatibility and summarized potential synergistic mechanisms. Method: An exhaustive search was conducted for potentially relevant studies in nine online databases. The selection criteria were based on the Participants, Interventions, Control, Outcomes, and Study designs strategy. The SYRCLE risk of bias tool for animal trials was used to perform the methodological quality assessment. RevMan V.5.3 and STATA/SE 15.1 were used to perform the meta-analysis following the Cochrane Handbook for Systematic Reviews of Interventions. Result: 24 studies were included in the systematic review and meta-analysis. 12 outcomes were evaluated in the meta-analysis, including BNP, HR, HWI, ALD, LVEDP, LVSP, EF, FS, +dP/dtmax, −dP/dtmax, TNF-α and the activity of Na + -K + -ATPase. Subgroup analyses were performed depending on the modeling methods and duration. Conclusion: The synergistic Fuzi compatibility therapeutic effects against CHF animals were superior to those of Fuzi alone, as shown by improvements in cardiac function, resistance to ventricular remodeling and cardiac damage, regulation of myocardial energy metabolism disorder and RAAS, alleviation of inflammation, the metabolic process in vivo, and inhibition of cardiomyocyte apoptosis. Variations in CHF modeling methods and medication duration brought out possible model–effect and time-effect relationships.